Pengaruh Media Kinetic Sand terhadap Motorik Halus Siswa Cerebral Palsy - Ajeng Pradhita Septiningtyas; Renalatama Kismawiyati; Bhennita Sukmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of Kinetic Sand on the fine motor skills of first-grade students with cerebral palsy. A quantitative experimental method was employed using a one-group pretest-posttest design. The pretest results showed scores of DA (37.5), DI (31.25), AM (37.5), IL (43.75), and VA (37.5), with a mean of 37.5. Following the intervention, posttest results indicated score increases to DA (62.5), DI (56.25), AM (81.25), IL (81.25), and VA (87.5), with a mean of 73.75. Data were analyzed using the non-parametric Sign Test. The calculation yielded a Z-value of 2.236, indicating that all subjects experienced a positive improvement in their abilities. The study concludes that Kinetic Sand has a significant effect on improving the fine motor skills of students with cerebral palsy at SLB Negeri Cindogo Bondowoso. Keywords: Kinetic Sand; Fine Motor Skills; Cerebral Palsy